Commercial integrated library systems used in selected academic and special libraries - Esposo, Sharon Ma. S. 1964- (1999)
All the respondents said their expectations on the integrated library system were met. The system has performed as expected. Almost all of the respondents were satisfied with the integrated library system. Only one was not satisfied with the system currently used in their library.
Based on the study, the integrated library system is an indespensible ingredient to attain better service and work efficiently, which are primary policy objectives of libraries. Therefore, when considering an automated system for the library, an integrated system should be chosen because it allows the modules to interface and work with both independently of and concurrently with each other. The need for careful and rigorous automation planning process cannot be overemphasized. Intensive planning, assessing needs, goals and objectives, system study (system analysis and design), careful evaluation and selection of a system are all important for any integrated library system to succeed.
Seven academic and special libraries in the Phililppines were surveyed and these include:Asian Development Bank, UP college of Law, UP College of Science, De La salle University, International Rice Research Institute, University of San Carlos and Xavier University. The Chief librarians were the respondents of the study. In most cases, the information technology staff of the library assisted the chief librarian in answering the questionnaire. Six commercial integrated library systems software were examined in this study namely: VTLS, INNOPAC, GEAC, FOLLET, TINLAW and T-SEREIS. The descriptive method was used with a structured-questionnaire as a data-gathering tool. The questionnaire was divided into the following parts according to the objectives set forth in the study: 1. Background of the integrated library system software; 2. Policies and reasons in adapting/adopting an integrated library system; 3. Steps and activities undertaken during the system study; 4. Steps and activities carried out in the selection of the system software; 5. Problems encountered and actions taken; and lastly, 6. Perception of the integrated library sytem currently being used and librarians' level of satisfaction with the system.
The data gathered were tabulated, tallied, analyzed, and interpreted using frequencies, percentages and mean ranking to carry out the objectives of the study.
The specific objectives of the study are: 1) to determine the policies and reasons adapted/adopted by the libraries in choosing an integrated library system; 2) to determine the activities carried out in studying the automation need of the library; 3) to determine the steps and activities carried out in evaluating and choosing a commercial integrated system; 4) to identify problems encountered during the implementation of the library system and corresponding interventions to address them; 5) to find out the perception of the librarians about the overall performance of the commercial library system, and 6) to measure the level of satisfaction of librarians with the system currently being used.
This study is a survey of the different commercial integrated library systems used in selected academic and special libraries. The purpose of this study is to describe the activities and experiences undertaken by seven libraries in choosing and implementing an integrated library system currently being used in their libraries.
Computer print out.
Vita
Thesis (M.L.I.S.)--University of the Philippines, Diliman
Keywords: Integrated library systems (Computers).; Academic libraries--Philippines--Automation.; Special libraries--Philippines--Automation.